RANCANGAN SISTEM MONITORING PENGIRIMAN BARANG BERBASIS WEBSITE PADA PT. DENSO CENTRA - Septiana Ningtyas; Harun Ar-Rasyid; Anugrah Marchiandy (Institut Teknologi dan Bisnis (ITB) Swadharma, 2022)
The purpose of this research is to design a delivery information system for Denso Centra company. PT. Denso Centra is a company engaged in the sale of auto spare parts. In the delivery process to the customer's location, couriers often forget the customer's location and in reporting shipments there are often queues. Based on the analysis using the PIECES framework, it can be concluded that the main problem of PT. Denso Centa is the accuracy and efficiency of information that is less than the maximum on the running system so by making this web-based system it is hoped that it can produce better information. With the design of a website-based application program at PT. Denso Centra, is expected to help simplify the management of data on the delivery of goods and speed up the process of making reports to the leadership. The results of the modeling are in the form of use case diagrams, class diagrams, activity diagrams, and sequence diagrams. While the software used is the PHP and MySql Web programming languages and Micro Dreamweaver. The results of the research are in the form of a web-based delivery system which is expected to overcome the problems that exist in the delivery of goods at PT Denso Centra